2010
DOI: 10.1371/journal.pone.0009683
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Therapeutically Attenuates Murine Bleomycin-Induced Pulmonary Fibrosis via Its Effects on Macrophages

Abstract: Macrophages promote tissue remodeling but few mechanisms exist to modulate their activity during tissue fibrosis. Serum amyloid P (SAP), a member of the pentraxin family of proteins, signals through Fcγ receptors which are known to affect macrophage activation. We determined that IPF/UIP patients have increased protein levels of several alternatively activated pro-fibrotic (M2) macrophage-associated proteins in the lung and monocytes from these patients show skewing towards an M2 macrophage phenotype. SAP ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 26 publications
4
140
0
Order By: Relevance
“…9,13,24 They have potential to differentiate into (myo)fibroblasts in vivo in response to CCl 4 -induced liver injury 4 and into hepatic fibrosis in Abcb4-deficient mice. 25 Inhibition of fibrocyte recruitment by human serum amyloid protein significantly attenuates fibrogenesis in liver (our unpublished observation), lungs, 7 and kidneys. 8 Similar to BDL, hepatotoxic injury triggers migration of fibrocytes to the damaged liver.…”
Section: Migration Of Fibrocytes Is Mediated By Chemokine Receptorsmentioning
confidence: 76%
See 1 more Smart Citation
“…9,13,24 They have potential to differentiate into (myo)fibroblasts in vivo in response to CCl 4 -induced liver injury 4 and into hepatic fibrosis in Abcb4-deficient mice. 25 Inhibition of fibrocyte recruitment by human serum amyloid protein significantly attenuates fibrogenesis in liver (our unpublished observation), lungs, 7 and kidneys. 8 Similar to BDL, hepatotoxic injury triggers migration of fibrocytes to the damaged liver.…”
Section: Migration Of Fibrocytes Is Mediated By Chemokine Receptorsmentioning
confidence: 76%
“…5 It has been demonstrated that CD45 ϩ and collagen ␣1(I) ϩ fibrocytes migrate to the injured liver in response to cholestasis 4 and comprise approximately 3% to 5% of the cells producing collagen type I. Despite low numbers, inhibition of fibrocyte recruitment via administration of human serum amyloid protein, 6 a natural inhibitor of fibrocyte migration and differentiation, effectively attenuated fibrosis in lungs, 7 kidneys, 8 and liver (our unpublished observation), emphasizing an important role for fibrocytes in fibrogenesis of parenchymal organs. A Phase II clinical trial is under way to assess the effectiveness of human serum amyloid protein in postsurgical fibrosis in patients with glaucoma.…”
mentioning
confidence: 99%
“…82 Injections of PTX2 reduce fibrosis significantly in several animal models (pulmonary fibrosis, ischemic cardiac fibrosis, renal fibrosis). [83][84][85][86][87][88] On the other hand, PTX3 promotes human and murine fibrocyte differentiation. 81 PRM-151 is a recombinant PTX2 being actively investigated in the treatment of various fibrotic diseases including MF (NCT01981850).…”
Section: Targeting Fibrogenic Cytokinesmentioning
confidence: 99%
“…These cells express elevated levels of scavenger receptors such as macrophage scavenger receptor (MSR) and mannose receptor C (MRC/ CD206) 69,70 . Assessing circulating primary cells from IPF patients, we have determined an elevation of CD163+CD14+ cells and M2-associated soluble mediators in the circulation, which was more pronounced in progressive IPF patients, suggestive of an overall elevated M2 background in these patients 71 . We have also shown that peripheral blood monocytes from patients with scleroderma-related lung disease display a pro-fibrotic phenotype, characterized by increased CD163 expression and CCL18 production 72 .…”
Section: Fibroblast Cell: Cell Interactionsmentioning
confidence: 99%
“…Therefore the Th2 cytokine profile observed in remodeled lungs contributes to the appearance of M2 macrophages. Studies of bleomycin-induced fibrosis have assessed either M2 macrophage or fibrocyte number 71,76 . It is increasingly recognized that there is some overlap between these cell subsets in terms of both function and markers 76 .…”
Section: Fibroblast Cell: Cell Interactionsmentioning
confidence: 99%